Validation of insomnia questionnaires in the general population: The Nord‐Trøndelag Health Study (HUNT). (27th October 2020) - Filosa, James; Omland, Petter Moe; Langsrud, Knut; Hagen, Knut; Engstrøm, Morten; Drange, Ole Kristian; Knutsen, Andreas Jarlalein; Brenner, Eiliv; Kallestad, Håvard; Sand, Trond
Abstract: The primary aim was to validate questionnaire‐based insomnia diagnoses from a modified Karolinska Sleep Questionnaire (KSQ) and the Insomnia Severity Index (ISI), by age category (< or >65 years), against a semi‐structured face‐to‐face interview. Secondary aims were to split validity by diagnostic certainty of the interview and to compare prevalence estimates of questionnaire‐ and interview‐based diagnoses. A total of 232 out of 1, 200 invited (19.3%) from the fourth Nord‐Trøndelag Health Study (HUNT4) completed questionnaires, including the KSQ and ISI, shortly before attending a face‐to‐face diagnostic interview for insomnia based on the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM‐5). Both a tentative (DSM‐5 criteria A–E) and a definite (criteria A–H) interview diagnosis was evaluated. Cohen's kappa statistic quantified questionnaire validity. In all, 33% (95% confidence interval 27–39%) of participants had definite insomnia: 40% of women and 21% of men. The ISI (cut‐off 12) and several KSQ‐based diagnoses showed very good validity ( κ ≤0.74) against the tentative, versus good validity ( κ ≤0.61) against the definite interview diagnosis. Short questionnaires, requiring a daytime symptom at least three times a week, may underestimate insomnia prevalence. Validity was consistently higher for persons aged below versus above 65 years (definite insomnia: κ ≤0.64 vs. κ ≤0.56). Our results have implications for epidemiological population‐based studies utilising insomnia questionnaires.